Building Critical and Moral Generation: The Implementation of HOTS Approach in Islamic Religious Education - Ahmad, Ahmad; Ruslan, Ruslan; Nasaruddin, Nasaruddin (Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the implementation of Higher Order Thinking Skills (HOTS) in Islamic Religious Education (PAI) learning at SMAN 4 Kota Bima. HOTS, which includes analytical, evaluative, and creative abilities, is expected to enhance students' critical, creative, and innovative thinking skills in the 21st century. Using a qualitative descriptive method, data were collected through interviews, observations, and document analysis. The findings indicate that key supporting factors for HOTS implementation include adequate infrastructure, teacher competence, and active student participation. However, challenges such as limited teacher understanding of HOTS, insufficient resources, and resistance to paradigm shifts in learning were identified. To optimize HOTS implementation, recommendations include improving teacher training, developing relevant curricula, and integrating educational technology and project-based assessments. The study concludes that, with proper support, HOTS can significantly improve the quality of learning and better prepare students to face global challenges. This research highlights the importance of HOTS in transforming PAI learning to meet the demands of the 21st century.